2017
DOI: 10.14302/issn.2575-1212.jvhc-17-1586
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Inflammatory Infiltrate Canine Mammary Carcinomas

Abstract: The mammary tumor is one of the most common cancer in female dogs and, at the present days, there is a big focus on the study of the relation between this kind of tumor in animals and the cells that stay around them,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…This immune signature was even much more pronounced for fresh tumoroids as demonstrated by the expression of T cell and macrophage markers (Granzyme B, Siglec1, and CD163). Previous studies have shown that CMT showed inflammatory infiltrate consisting predominantly of lymphocytes, macrophages, plasma cells, and mast cells supporting our proteomics findings [41]. These results suggest that the cellular diversity may be higher in fresh tumoroids and tumoroids made from frozen cells compared to cryopreserved tumoroids.…”
Section: Discussionsupporting
confidence: 91%
“…This immune signature was even much more pronounced for fresh tumoroids as demonstrated by the expression of T cell and macrophage markers (Granzyme B, Siglec1, and CD163). Previous studies have shown that CMT showed inflammatory infiltrate consisting predominantly of lymphocytes, macrophages, plasma cells, and mast cells supporting our proteomics findings [41]. These results suggest that the cellular diversity may be higher in fresh tumoroids and tumoroids made from frozen cells compared to cryopreserved tumoroids.…”
Section: Discussionsupporting
confidence: 91%